Integrating Different Types of Knowledge to Understand Temporal Changes in Reef Landscapes - Quirino-Amador, Maria Iohara; Longo, Guilherme Ortigara; Freire, Fúlvio Aurélio de Morais; Lopes, Priscila F. M. (Frontiers in Ecology and Evolution, 2021)
Reefs are highly diverse ecosystems threatened by anthropogenic actions that change their structure and dynamics. Many such changes have been witnessed by different reef users who hold specific knowledge about the reef landscape according to their experience and their uses. We aimed to understand whether fishers, divers, and marine scientists have different perceptions of general changes which have occurred in reefs and whether they show specific convergence or divergence in their knowledge. We conducted 172 semi-structured interviews with stakeholders from Northeast and Southeast Brazil where either coral or rocky reefs are found, respectively. These regions encompass a major part of the reefs occurring in the Southwestern Atlantic Ocean. Marine scientists and divers perceive that some coral species have undergone the sharpest declines among reef species and point out pollution and tourism as having the main negative impacts on reefs. On the contrary, fishers have noticed greater declines in fishing targets (i.e. groupers) and have hardly noticed differences in coral abundance or diversity over time. While divers have broader view of changes in reef resources, sharing some convergence both with marine scientists and fishers, marine scientists and fishers provide information on more specific groups and economically relevant resources, respectively. Nevertheless, the stakeholders generally agree that reef landscapes have been undergoing negative changes and loss of abundance in organisms. The complementarity of information from different stakeholders enables better understanding of the changes and impacts that affect reef environments.